1985
DOI: 10.1136/bmj.291.6489.176-a
|View full text |Cite
|
Sign up to set email alerts
|

Care by parents in hospital.

Abstract: admitted to the paediatric ward, representing 3-8% (17/439) of the infants under 1 year but 12% of the bed occupancy. Infants who had previously been in the neonatal intensive care unit accounted for a large proportion of the bed occupancy partly because they stayed in the ward longer for general problems (such as upper respiratory infections and social and feeding difficulties) than the other infants (table) and partly because a small number needed prolonged admissions for intensive treatment of chronic condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0
1

Year Published

1992
1992
2008
2008

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 3 publications
2
23
0
1
Order By: Relevance
“…Parents in the current study were active participants in care related to their child's ADL. This finding supports results of previous studies which identified parents' active participation in their children's ADL care (Algren, 1985;Balling, & McCubbin, 2001;Hill, 1978;Jackson et al, 1978;Kristensson-Hallstrom & Elander, 1994;MacDonald, 1969;Merrow & Johnson, 1968;Neill, 1996a;Webb et al, 1985). Four ADL activities were rated highly on both the Actual and Desired scales respectively: Helped with elimination (90.…”
Section: Discussion Of Findingssupporting
confidence: 81%
See 4 more Smart Citations
“…Parents in the current study were active participants in care related to their child's ADL. This finding supports results of previous studies which identified parents' active participation in their children's ADL care (Algren, 1985;Balling, & McCubbin, 2001;Hill, 1978;Jackson et al, 1978;Kristensson-Hallstrom & Elander, 1994;MacDonald, 1969;Merrow & Johnson, 1968;Neill, 1996a;Webb et al, 1985). Four ADL activities were rated highly on both the Actual and Desired scales respectively: Helped with elimination (90.…”
Section: Discussion Of Findingssupporting
confidence: 81%
“…In earlier studies, parents have reported providing more care than they desired due to their perception that it was expected of them by the nursing staff This distribution is also reflected in the IPP/HC-D, as "Spending quiet time interacting with the child" and "Comforting the child when upset" were also the most frequently reported Desired activities by parents (95.8% and 94.8% respectively). Earlier research has indicated that providing comfort is a priority for parents of hospitalized children (Algren, 1985;Dearmun, 1992;Hill, 1978;Jackson, Bradham, & Burwell, 1978;Kristensson-Hallstrom,& Elander, 1994;MacDonald, 1969;Merrow & Johnson, 1968;Coyne, 1995;Webb et al, 1985).…”
Section: Discussion Of Findingsmentioning
confidence: 99%
See 3 more Smart Citations